FORMATION OF STUDENTS' ABILITY TO THINK CREATIVELY BASED ON INTERNATIONAL ASSESSMENT STUDIES - Bakhtiyor Khabibullayevich Usmanov (Western European Studies, 2025)
This article examines information about the formation of students' creative thinking skills based on international assessment studies. At the same time, creative thinking, diagnostics of the educational process, improvement of educational programs, modernization of teaching methods, optimization of the assessment system, advanced training of teachers, strengthening cooperation with parents, the impact of international assessment studies on creative thinking, methodological foundations for the development of creative thinking, the development of divergent thinking, the main aspects of divergent thinking, interactive and project research and development approach, integration of international assessment research results into education, the role of international evaluative research, the importance of the methodology of using international evaluative research in the development of cognitive competence of students, methodological approaches to the use of international evaluative research in the development of cognitive competence of students are highlighted
Keywords: creative thinking; diagnostics; modernization; optimization